(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Aim and Background: In the present study was to find out the prevalence of tobacco consumption and factors contributed for tobacco consumption among males aged 15 years and above in Kanchipuram town. Human beings have been using tobacco since 600 A.D. It was introduced in Europe by Columbus who came to know about it from the Caribbeans during his historical journeys. It was introduced in India by the Portuguese. Materials and Methods: This is Community based cross sectional study was conducted in Kanchipuram town. All the study subjects were explained in detail about the purpose and methodology of the study and were fully assured of strict confidentiality. Informed oral consent was obtained. Personal interview questionnaire is administered and obtained the demographic details and tobacco consumption. Kanchipuram district has been divided into 4 revenue divisions comprising of 11 taluks with 1137 revenue villages. For development reasons, it is divided into 13 development blocks with 648 Village Panchayats. Results: The present study showed a high prevalence of 55.4% tobacco use among male ever users aged 15 years and above in Kanchipuram town. A prevalence of 34% has been noted in male current users of the same age group. Conclusion: In the Present study we conclude that the high prevalence of use of tobacco among males age 15-and above is a major and public health problems. This affects the coming generation also. Hence steps need to be taken right now to tackle this problem.